Fracture Mechanics-based Assessment of Welded Joints in Structural Steel Components - Tejasvi Arneja; Mayank Yadav (International Journal of Fracture Mechanics and Damage Science, 2024)
In many engineering applications, connection by welding are essential to the structural integrity of steel components. However, because of the intricate interplay between material qualities, welding techniques, and structural stress conditions, evaluating the dependability and safety of these welded connections continues to be a difficult challenge. A systematic framework that evaluates the behavior of cracks and faults in welded joints is provided by fracture mechanics, which also offers insights into the initiation, propagation, and determination of critical flaw size. The assessment methods for welded joints in structural steel components that are based on fracture mechanics are thoroughly reviewed and analyzed in this research paper. There includes discussion of several experimental, computational, and analytical techniques for fatigue gauges, crack growth analysis, and fracture toughness characterisation. Moreover, case studies and application examples show how useful fracture mechanics-based methods are for improving our comprehension and ability to predict the behavior of welded joints, which in turn leads to better practices for welding steel structure maintenance, scrutiny, and design.
Keywords: Steel; Welding; crack growth; fracture mechanics; skyscrapers